Clinical Analysis of 17 Cases of Borderline Ovarian Tumors During Pregnancy - Wang, Mingdan; Li, Yue; Xu, Tongtong; Shi, Chen; Jiang, Lili; Liu, Kuiran (Frontiers in Oncology, 2022)
Abstract Objective: To retrospectively analyze the clinical characteristics and prognosis of 17 cases of pregnancy complicated with borderline ovarian tumors, to provide help for clinical workers. Materials and methods: The clinicopathological data of 17 patients with ovarian borderline tumors during pregnancy in Shengjing Hospital of China Medical University from January 2015 to June 2021 were collected and analyzed retrospectively. Results: Among the 17 patients, 4 underwent surgery in the early stage of pregnancy, of which 2 underwent conservative surgery and induced abortion at the same time. One case underwent unilateral adnexa + contralateral cyst enucleation. After normal pregnancy to full-term pregnancy, one healthy live baby was delivered by cesarean section. One case of tubal pregnancy underwent enucleation of ovarian cyst and right salpingectomy. Two patients underwent the operation in the second trimester of pregnancy. After a conservative operation to full-term cesarean section, the newborn was healthy.11 cases underwent surgery in the third trimester of pregnancy, of which 1 case underwent right appendectomy due to cyst enlargement at 28 weeks of pregnancy. A healthy live baby was delivered by cesarean section from 38 weeks of pregnancy; One case underwent cesarean section and right appendectomy at 32 weeks of pregnancy due to cyst rupture; One case underwent cesarean section + left adnexectomy + right ovarian dissection due to the gradual enlargement of the cyst; The other 8 cases were accidentally found during cesarean section due to the indication of obstetric cesarean section, of which 3 cases of malignant transformation underwent the comprehensive staged operation. The patient had no recurrence after regular reexamination, and the newborns were healthy. Conclusion: Preoperative diagnosis of borderline ovarian tumors in pregnancy is delayed, and imaging and tumor markers are not specific. The coincidence rate between intraoperative frozen pathology and postoperative paraffin pathology is not high. Borderline tumors are mainly treated by surgery, and the prognosis of mothers and infants is good.